Sudan bland stormakter : En jämförande fallstudie av Rysslands, Kinas och USA:s utrikespolitiska strategier i Sudan. - Jöhnsson Widerberg,Wilma (2025)
This thesis investigates the dynamics of great power involvement in Sudan, focusing on strategic actions and alliances of global powers in the region. The objective of the study is to analyze economic, political and military interests and means in Sudan through the lens of realistic values and beliefs. By utilizing neoclassical realism, the security dilemma and classical geopolitics, this study analyses the complex relations between Sudan and global actors, including the United States, China and Russia. By delving into the interactions between these states, this thesis highlights how foreign policy strategies are played out in peripheral regions and what motivates these actions. Furthermore, the study provides insight into the ways smaller states like Sudan can be used as an arena for great power competition and fall victim due to its geopolitical advantages. Ultimately, the research illustrates how global superpowers use small states as chess pieces in the larger game of international anarchy. By understanding the role of Sudan in this dynamic, the thesis contributes to a nuanced comprehension of the intersectionality between security, international relations, and great power politics.
Keywords: Stormakter; Maktbalans; Great Power Competition; Neoklassisk realism; Säkerhetsdilemmat; Klassisk geopolitik; Utrikespolitisk strategi; Internationella relationer.